2009
DOI: 10.1001/archoto.2008.515
|View full text |Cite
|
Sign up to set email alerts
|

Airway Management in Children With Mucopolysaccharidoses

Abstract: Patients affected by MPSs require the vigilant attention of the otolaryngologist, as sleep apnea and upper airway obstruction are common complications. Successful bone marrow engraftment may alter the natural history of airway disease and result in substantial improvement in symptomatic airway disease in children with MPSs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
1
9

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(77 citation statements)
references
References 26 publications
1
66
1
9
Order By: Relevance
“…É bem conhecida a associação entre MPS e a ocorrência de hipertrofia adenotonsilar, língua volumosa e limitação da abertura bucal/anomalias mandibulares 5,[26][27][28][29][30] . Embora não tenha sido possível a avaliação da prevalência de hipertrofia adenotonsilar, os demais achados foram frequentes na amostra estudada.…”
Section: Alteração N (%)* N (%) N (%) Punclassified
See 1 more Smart Citation
“…É bem conhecida a associação entre MPS e a ocorrência de hipertrofia adenotonsilar, língua volumosa e limitação da abertura bucal/anomalias mandibulares 5,[26][27][28][29][30] . Embora não tenha sido possível a avaliação da prevalência de hipertrofia adenotonsilar, os demais achados foram frequentes na amostra estudada.…”
Section: Alteração N (%)* N (%) N (%) Punclassified
“…Embora não tenha sido possível a avaliação da prevalência de hipertrofia adenotonsilar, os demais achados foram frequentes na amostra estudada. Eles trazem consigo um risco aumentado, para os pacientes, de ocorrência de respiração oral e de apneia obstrutiva e outras alterações do sono, além de uma maior necessidade de adenoidectomias e amigdalectomias [26][27][28][29][30] , também presentes nesta amostra. Contudo, é importante frisar que a maioria dos pacientes avaliados apresentou abertura normal de mandíbula.…”
Section: Alteração N (%)* N (%) N (%) Punclassified
“…In severe cases, such operations are impossible due to potential complications arising of anesthesia or surgical intervention [15]. Severe sleep respiratory disorders may be treated with continuous positive airway pressure (CPAP), when high-pressure air is pumped in the mask; this prevents airway collapse during respiration, improves sleep quality, reduces dyspnea and normalizes blood gas concentration [16,17]. …”
Section: Resultsmentioning
confidence: 99%
“…Similarly to our study, Yeung et al (2009) used FFL and PSG to assess some patients with different types of MPS. They found that 19 of their 27 patients presented with upper airway obstruction.…”
Section: Discussionmentioning
confidence: 99%